2018
DOI: 10.1111/php.12914
|View full text |Cite
|
Sign up to set email alerts
|

Improved Wound Remodeling Correlates with Modulated TGF‐beta Expression in Skin Diabetic Wounds Following Combined Red and Infrared Photobiomodulation Treatments

Abstract: Diabetic wounds are a major cause of morbidity among patients with poorly controlled blood glucose levels. Conventional empirical wound care strategies have shown limited efficacy, and there is an urgent need to develop novel therapeutic strategies. Photobiomodulation treatments have shown positive therapeutic effects in several cell culture and animal models. In this study, we examined wound healing in diabetic rats following treatments with two laser wavelengths, namely red (660 nm) and infrared (808 nm) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…This is because the biological effects of PBM are influenced by many factors, such as wavelength, energy density, and cell/tissue type. For example, the TGF-β signaling pathway plays important roles in both wound healing and tissue fibrosis (Dang et al, 2011;Fekrazad et al, 2018). PBM has been shown to stimulate the TGF-β pathway to enhance cell proliferation and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the biological effects of PBM are influenced by many factors, such as wavelength, energy density, and cell/tissue type. For example, the TGF-β signaling pathway plays important roles in both wound healing and tissue fibrosis (Dang et al, 2011;Fekrazad et al, 2018). PBM has been shown to stimulate the TGF-β pathway to enhance cell proliferation and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a soluble factor that is one of the key regulators of angiogenesis, which binds to the VEGF receptor to induce the proliferation and migration of vascular endothelial cells via autocrine and paracrine pathways, ultimately regulating neovascularization (2,4,16,44). Additionally, TGF-β1 serves a key role in wound healing by mediating the chemotaxis of inflammatory cells, the differentiation and proliferation of fibroblasts, and the production and degradation of collagen and extracellular matrix (19,20,45). Decreased expression and dysfunction of TGF-β1 and its receptors may hamper wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…During the early stages of wound healing, the overexpression of inflammatory factors, such as interleukin (IL)-6 and tumor necrosis factor (TNF)-α (14,15), severely impairs the formation of granulation tissue and further delays wound healing. However, a number of studies have revealed that growth factors, including vascular endothelial growth factor (VEGF) (2,4,16), epidermal growth factor (17,18) and transforming growth factor-β (TGF-β) (19,20), serve an important role in the promotion of wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of growth factors and cytokine release and expression has been reported in irradiated cells. These growth factors and cytokines include transforming growth factor‐beta (TGF‐β), 61‐63 PDGF 64 and TNF‐α 65,66 which regulates the stimulation of cell growth, cellular differentiation, and inhibition of melanocyte differentiation to speed up the wound‐healing process.…”
Section: Photobiomodulation Therapymentioning
confidence: 99%
“…Fekrazad et al 66 in a more recent study investigated the role of PBM using two different wavelengths (red 660 nm and infrared 808 nm in combination and individually) on a diabetic animal model. The results of this study showed that the combination of both laser treatments led to a decrease in TGF‐β1 levels during the wound healing process.…”
Section: Photobiomodulation Therapymentioning
confidence: 99%